Effects of a powder made from three medicinal plants on growth performance, intestinal health, antioxidant activity, and anti-inflammatory ability in Xianghuang chickens - Yang, Can; Tang, XiaoWu; Wu, RunTao; Jiang, YunMiao; Quan, Qi; Xiao, YuTian; Kuang, JiaXuan; Chen, JiaYi; Tang, QingHai; Jiang, Zhi (Frontiers in Veterinary Science, 2025)
This study investigated the effect of a traditional Chinese medicine (TCM) plant powder made from an equal proportion of Sarcococca ruscifolia Stapf, Hedera nepalensis var. sinensis (Tobl.) Rehd, and Clematis chinensis Osbeck on growth performance and intestinal health in Xianghuang chickens, focusing on intestinal histomorphology, antioxidant activity, and anti-inflammation function. A total of 100 10-day-old male Xianghuang chickens were randomly assigned to two groups, with five replicate cages per group containing 10 birds each. The birds in the control group received a corn-soybean–based diet, while the birds in the TCM group received the control diet supplemented with 2% of the TCM powder. The chickens were slaughtered for sample collection on D28. The results showed that the average daily feed intake (ADFI), average daily gain (ADG), and feed-to-gain (F:G) ratio were not affected by the TCM supplementation (p > 0.05). In the jejunum and ileum, the ratio of the villus height to the crypt depth was higher in the TCM group compared to the control group (p < 0.05). Supplementing the chickens with 2% TCM powder increased the total superoxide dismutase (T-SOD) and catalase (CAT) activities in the jejunal mucosa compared to the control group (p < 0.05). The gene expression of tumor necrosis factor alpha (TNF-α) was downregulated in the jejunal mucosa and spleen in the TCM group compared to the control group (p < 0.05). In conclusion, TCM powder can be safely utilized to promote the development of the intestinal tract by enhancing antioxidant and anti-inflammatory functions without affecting the growth performance. Our findings suggest that TCM powder is an effective and low-toxicity natural additive for intestinal improvement in poultry.